2017
DOI: 10.1111/pirs.12215
|View full text |Cite
|
Sign up to set email alerts
|

Neighbour regions as the source of new industries

Abstract: The development of new industries demands access to local capabilities. Little attention has yet been paid to the role of spillovers from neighbour regions for industrial diversification, nor has the role of network linkages between neighbour regions been investigated. As the spread of capabilities has a strong geographical bias, we expect regions to develop new industries in which their neighbour regions are specialized. To test this hypothesis, we analyse the development of new industries in US states during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 53 publications
1
61
0
3
Order By: Relevance
“…Ezcurra and Rios (2015) in turn took a sample of 272 European regions from 1991 to 2001 and used spatial econometric techniques to demonstrate the negative correlation, which is partly influenced by the volatility of spatial spillovers of neighbouring regions. Such spillover effects are recently confirmed by Boschma, Martin, and Minondo (2017) using a data set on the development of new industries in US states during 2000-2012. As neighbour regions are the source of new industries, regions specialize similarly and share the same economic instability and industrial diversification opportunities.…”
Section: Industrial Diversification Of Gross Value Addedmentioning
confidence: 75%
“…Ezcurra and Rios (2015) in turn took a sample of 272 European regions from 1991 to 2001 and used spatial econometric techniques to demonstrate the negative correlation, which is partly influenced by the volatility of spatial spillovers of neighbouring regions. Such spillover effects are recently confirmed by Boschma, Martin, and Minondo (2017) using a data set on the development of new industries in US states during 2000-2012. As neighbour regions are the source of new industries, regions specialize similarly and share the same economic instability and industrial diversification opportunities.…”
Section: Industrial Diversification Of Gross Value Addedmentioning
confidence: 75%
“…Of course, the transmission of knowledge is heavily constrained by geographical distance, and tends to take place among regions that are geographically proximate to one another (Boschma et al . ). Bahar et al .…”
Section: Introductionmentioning
confidence: 97%
“…Boschma et al . () have concluded that industrial structures of neighbouring states in the US are more similar to each other.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations